PENGARUH UNSUR-UNSUR PEMBENTUK PERILAKU TERHADAP PARTISIPASI DALAM MENDIRIKAN IJIN MENDIRIKAN BANGUNAN (IMB) DI KECAMATAN UNGARAN BARAT - Retna Hermana; Hardi Warsono; Mochammad Mustam (Journal of Public Policy and Management Review, 2014)
such a way that it regularly. One of the spatial is by issuing building permits, here in after abbreviated IMB. To achieved development result could sustainable, much said that a participatory approach neede to explained the its logic and strategic. The problem that often arises is there are some people who wouldn’t participate by making IMB, it’d showed by how much people didn’t have IMB. The research methods used was quantitative with descriptive correlative approach. The elements to form behaviour has positive and significant relation to participation in making IMB. It could be seen by the result from Kendall analytic where there was sig 0,000 which is smaller than 0,01; coefficient 0,151 when it meant the elements to form behaviour with participation in making IMB move in same motion. There was determination coefficient 2% between elements to form behaviour with participation in making IMB which showed how much effect between those two. So it meant that there was effects elements to form behaviour for the participation in making IMB in Ungaran Barat especially Bandarjo.